Combustion Synthesis of FeAl-based Composites from Thermitic and Intermetallic Reactions - Chun-Liang Yeh (Crystals, 2019)
Combustion syntheses involving intermetallic and thermitic reactions were conducted to fabricate FeAl–TiB2–Al2O3 composites. Two combustion systems consisting of Fe, Al, Ti, Fe2O3 and B2O3 were studied for formation of xFeAl–yTiB2–Al2O3 composites with x = 1.5–3.5 and y = 0.5–0.8. In the reaction series, thermitic reduction of Fe2O3 and B2O3 by Al thermally activated the reaction between Fe and Al. As a result, the combustion wave of the synthesis reaction was sufficiently exothermic to propagate in a self-sustaining manner. With an increase in TiB2 and FeAl of the composites, the decrease of reaction exothermicity resulted in a decline of the combustion wave velocity and reaction temperature. The activation energy Ea = 88.92 kJ/mol was deduced for the synergetic combustion reaction. Based on XRD analysis, a thorough phase conversion was achieved and composites composed of FeAl, TiB2, and Al2O3 with different contents were obtained. The SEM micrograph showed the FeAl-based composite with a dense and connecting morphology.